New Perspectives on the Guaranteed Income - Karl Widerquist (Levy Economics Institute of Bard College, 1999)
Renewed interest in a guaranteed income is evident from the number of books that have been published on the topic in the 1990s. This paper discusses and compares seven of those books: Arguing for Basic Income: Ethical Foundations for a Radical Reform, edited by Philippe Van Parijs; Real Freedom for All: What (If Anything) Can Justify Capitalism? by Philippe Van Parijs; Public Economics in Action: The Basic Income/Flat Tax Proposal, by A. B. Atkinson; The 30,000 Solution, by Robert R. Schutz; The Benefit of Another's Pains: Parasitism, Scarcity, Basic Income, by Gijs Van Donselaar; "...And Economic Justice for All" Welfare Reform for the 21st Century, by Michael L. Murray; and The National Tax Rebate: A New America with Less Government, by Leonard M. Greene.
Keywords: 330